A point mutation in the hair cell nicotinic cholinergic receptor prolongs cochlear inhibition and enhances noise protection - Taranda, Julian (2009)
The transduction of sound in the auditory periphery, the cochlea, is inhibited by efferent cholinergic neurons projecting from the brainstem and synapsing directly on mechanosensory hair cells. One fundamental question in auditory neuroscience is what role(s) this feedback plays in our ability to hear. In the present study, we have engineered a genetically modified mouse model in which the magnitude and duration of efferent cholinergic effects are increased, and we assess the consequences of this manipulation on cochlear function. We generated the Chrna9L9′T of knockin mice with a threonine for leucine change (L9′T) at position 9′ of the second transmembrane domain of the α9 nicotinic cholinergic subunit, rendering α9-containing receptors that were hypersensitive to acetylcholine and had slower desensitization kinetics. The Chrna9L9′T allele produced a 3-fold prolongation of efferent synaptic currents in vitro. In vivo, Chrna9L9′T mice had baseline elevation of cochlear thresholds and efferent-mediated inhibition of cochlear responses was dramatically enhanced and lengthened: both effects were reversed by strychnine blockade of the α9α10 hair cell nicotinic receptor. Importantly, relative to their wild-type littermates, Chrna9L9′T/L9′T mice showed less permanent hearing loss following exposure to intense noise. Thus, a point mutation designed to alter α9α10 receptor gating has provided an animal model in which not only is efferent inhibition more powerful, but also one in which sound-induced hearing loss can be restrained, indicating the ability of efferent feedback to ameliorate sound trauma.